Environmental education for sustainable development in engineering education in Colombia - Acosta-Castellanos, Pedro Mauricio; Queiruga-Dios, Araceli; Camargo-Mariño, Julian A. (Frontiers in Education, 2024)
Environmental education (EE) is well known and extensively studied in Latin America, particularly in Colombia. Its application has been promoted and encouraged by governments through educational policies and regulations at all educational stages. On the other hand, thanks to the Sustainable Development Goals (SDGs), Education for Sustainable Development (ESD) is gaining increasing importance globally. This research aims to support theoretical findings that demonstrate the lack of knowledge, application, and research of ESD in engineering programs in higher education. Simultaneously, our study intends to measure the degree of acceptance of ESD compared to EE among engineering students in Colombia.Based on our results, a proposal was designed to address sustainable development (SD) within engineering degrees while providing a smoother transition between EE and ESD. A survey was conducted among 406 students from 8 universities in Colombia that offer engineering at the undergraduate level. The survey included Likert scale questions and openended questions. It was possible to identify the roots of EE in the engineering programs at Colombian universities and the progressive integration of ESD within engineering curricula and teaching. On the other hand, the converging areas within EE and ESD should be identified according to the information provided by students, which is unusual for a conservationist field such as EE compared to a developmental one like ESD. This research highlights several problems faced by engineering education in Colombia. The first is the limited knowledge students have about ESD and, consequently, SD. Secondly, there is a lack of academic areas or subjects that promote the knowledge and application of ESD. Finally, considering the unique findings in this study, a transition strategy between EE and ESD is proposed for Colombian higher education.